POLA PENDIDIKAN HAK ASASI MANUSIA DALAM AL-QUR’AN - Khumaidi Ali, Muh.; Abubakar, Achmad; Mahfudz, Muhsin (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
The Qur’an is a guide in all aspects of life. Not only for Muslims, but for all mankind, as reflected in the expression of Islam as rahmatan lil ‘alamin. One of the aspects contained in the verses of the Qur’an as a guide is the theme of human rights. Da'wah to raise human awareness about the important meaning of respect for human rights is reflected in the pattern of human rights education in the Qur'an. The definition of the pattern of human rights education in the Qur’an is a number of Qur’anic verses that talk about human rights and how the Qur’an invites people to respect those human rights.